Calculation of nutrients balance in the soils of the Ros River agroecosystem - Ukhan, Olha; Byletska, Svitlana; Osadcha, Nataliia; Luzovitska, Yuliia (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Introduction. The Ukrainian agricultural sector is dominated by farms and enterprises (69%), livestock productions are concentrated in households - 64%. The total amount of fertilizer applied to agricultural land over the year is an important factor in assessing the environmental impact of agriculture. Excessive nutrients in the soil pose a potential risk of leaching during the formation of water runoff and subsequent flow into the water body, which can lead to eutrophication of water bodies. Agricultural land in the Ros River catchment area covers 73% of the total territory of the river basin, of which 80% is sown with various crops. Aim of the research is to assess the impact of agricultural activities on the formation of the nutrients (nitrogen and phosphorus compounds) balance in soils in the Ros River watershed within the administrative units such as regions (4 in total) and districts (23 in total). Scientific novelty. The results of modern research on the balance of nitrogen and phosphorus in the Ros River agrosystem are presented for the first time in this paper. Practical value. The study is carried out for environmental purposes to establishbasic criteria for identifying vulnerable areas to agricultural nutrient accumulation and to further identify potential risks of surface water pollution and develop measures to prevent water eutrophication. Methods. The balance of nitrogen and phosphorus in soils was defined as the difference between the total supply them with fertilizers and their removal with crop yields. The income and expense sides of the balance sheet were calculated using special formulas. Calculations were made on the basis of statistical data on the number and types of animals, sown areas and crop yields, and the use of mineral and organic fertilizers for the periods of 2018 and 2020. Within the Ros River basin, data from the annual reports of the four oblasts statistical departments (Kyivska, Cherkaska, Vinnytska, and Zhytomyrska) by administrative districts were used. Results and conclusions. The calculations based on statistical information revealed that the weighted average nitrogen balance in the soils of the Ros River basin during the study period was in excess and averaged 13 kg N/ha; the phosphorus balance, on the other hand, was characterized by a deficit state and was equal to -28 kg P/ha. The load of nitrogen compounds was formed due to the supply of both organic fertilizers (2018) and mineral fertilizers (2020). The largest formation of nitrogen of organic origin was observed in Vasylkiv district of Kyiv region and Kaniv district of Cherkasy region (up to 84 kg/ha on average), where branches of powerful agricultural holdings are located. The highest dose of nitrogen fertilizers (87 kg N/ha) in 2018 was recorded in Pohrebyshche district of Vinnytsia region. In 2020, the largest amount of nitrogen fertilizers (206 kg N/ha) was applied in Koziatyn district of Vinnytsia region. The load of phosphorus compounds was mainly formed due to the development of poultry farming and amounted to 92% of the total share. The highest intake of phosphorus compounds of organic origin (over 80 kg P/ha) was in Vasylkiv district of Kyivska region and Kanivskyi district of Cherkaska region due to the location of the largest agricultural holdings in Ukraine – “Yasensvit” and “Nasha Ryaba”.